Renal Replacement Therapy in Intensive Care Unit at a Tertiary Care Center in Nepal - Chhetri, Pramod Kumar; Manandhar, DN; Poudel, P; Baidya, S; Raju, SB; Agrawaal, KK (Nepal Medical College Journal, 2019)
Acute kidney injury is a major complication in intensive care unit patients. It is associated with increased in-hospital mortality and length of stay. The provision of renal replacement therapy in intensive care is not widely available in resource poor countries like Nepal. The study aims to look into clinical profile and outcome of patients who received renal replacement therapy in intensive care unit. It was an observational study done from 1st October 2016 till 30th September 2017. Patient’s demographic data, indications, biochemical tests, outcomes, modality of renal replacement therapy were recorded. Statistical package for the social sciences version 17 was used for statistical analysis. There were total of 649 admissions in intensive care, among which 148 had kidney related complications. Of 148 patients, 69 (47%) received renal replacement therapy. Mean age, urea and creatinine on admission were 50.17 ± 18.42 years, 174.54 ± 63.46 mg/dl and 8.05 ± 3.49 mg/ dl respectively. They underwent 4.32 ± 3.09 sessions and 14.94 ± 10.88 hours of renal replacement therapy. Total 42 (61%) had septic shock on admission and underwent sustained low efficiency dialysis as the modality of renal replacement therapy. In-hospital mortality was 19 (28%). Presence of septic shock on admission and mean number of ionotropes required 2.05 ± 1.12 was statistically significant for in-hospital mortality (p=0.01). About half of the patients were on mechanical ventilation which was statistically significant for in-hospital mortality (p<0.001). Sustained low efficiency dialysis can be done in patients on ionotropes and patients can be switched over to intermittent hemodialysis.